Ascites in Breast Cancer: Progression from Negative Cytology to Avid Peritoneal Involvement - Duraksh Arshad; Sana Munir Gill; Taha Mehmood; Aamna Hassan (Journal of the Pakistan Medical Association, 2025)
Malignant ascites is caused by various factors such as lymphatic obstruction, increased vascular permeability and immune response. It presents a significant clinical challenge to the treating physicians considering limited treatment options resulting in increased morbidity and mortality. It is mostly associated with gastrointestinal, gynaecological, breast, hepatobiliary, and lung carcinomas. Paracentesis is usually important in determining the quantity and etiology of ascites. However, unlike conventional radiological imaging, 18F-FDG PET-CT can act as an early pointer towards its diagnosis. We present a case of breast ovarian syndrome highlighting the utility of hybrid nuclear imaging in solving this diagnostic dilemma. Keywords: Malignant ascites, breast cancer, cytology.